Pelvetia canaliculata as an aquafeed supplement for gilthead seabream Sparus aurata: A biorefinery approach for seaweed biomass valorisation - Pires, Damiana (2022)
For sustainable and economically viable aquaculture, it is necessary to search for alternative sources of aquafeeds. Algae have been studied because of their bioactive compounds with several activities such as antioxidants. The direct incorporation of the macroalgae Pelvetia canaliculata in sunflower oil to increase oxidative stability and biological value results in waste with high nutritional value that may be used as an ingredient in aquaculture feed. This study aimed to evaluate the effect of incorporating algae powder (PEL 1%, PEL 10%) and algae waste obtained after sunflower oil supplementation (WO 1%, WO 10%) in aquafeeds for gilthead seabream. We studied the growth performance, haematological profile, oxidative stress and metabolic parameters, and intestine histomorphology. Experimental diets did not influence growth performance or somatic indexes, and barely affected the haematological profile. Catalase showed higher activity in seabream fed with PEL10 than with control diet. Total glutathione had a higher activity in fish fed with both WO diets. Plasmatic levels of cholesterol were higher in PEL1 and WO10. Triglyceride levels were higher in WO1 and total lipids were higher in both WO diets. The histomorphology of the intestine was slightly modulated by experimental diets but was not affected negatively. In general, supplementation with Pelvetia powder and algal waste oil may be used as an aquafeed for gilthead seabream according to the results obtained for growth, some haematological parameters, catalase and total glutathione, intestinal villi length, and the number of total and acid goblet cells.